METHYL MERCURY PRODUCTION IN NATURAL-COLLECTED SEDIMENT WITH DIFFERENT GEOCHEMICAL PARAMETERS - Markus T. Lasut; Hardin F. Rares; Yoshiaki Yasuda (Universitas Gadjah Mada, 2009)
Production of methyl mercury (MeHg) has been shown in laboratory experiments using mercuric chloride (HgCl2) compound released into natural-collected sediments with different geochemical conditions. While the HgCl2 concentration was 30 µl of 113 ppm of HgCl2, the geochemical conditions [pH, salinity, total organic content (TOC), sulfur] of sampled sediments were A: 8.20, 0.00 ppt, 1.97%, and 0.92 ppt, respectively; B: 7.90, 2.00 ppt, 4.69%, and 1.98 ppt, respectively; and C: 8.20, 24.00 ppt, 1.32 %, and 90.90 ppt, respectively. A control was set with no HgCl2. Samples and control were incubated in room temperature of 27 ± 1 °C. Observations were done along 9 days with interval of 3 days. While total Hg was measured using mercury analyzer with Cold Vapor-Atomic Absorbtion Spectrophometer (CV-AAS) system, MeHg was measured by using a gas chromatograph with ECD detector after extracted by dithizone-sodium sulfide extraction method. The result shows that MeHg was found in both treatment and control experiments. The concentrations of the MeHg varied according to the geochemical condition of the sampled sediments. Peak production of MeHg occurred on the third day; however, the production was not significantly affected by the incubation time. Optimum production was found inversely related to the pH, in which highest and lowest the pH formed an ineffectively methylated mercury species. The TOC was significantly correlated to the optimum production. Salinity and sulfate contents were found not correlated to the optimum of MeHg production.